Amide‐Directed Bay‐Region Two‐Step Annulative π‐Extension (APEX) of Biphenyls and Terphenyls with Diaryliodonium Salts: Efficient Access to Polycyclic Aromatic Hydrocarbons. Issue 1 (26th November 2019) - Peng, Qiong; Zhang, Wen; Zhao, Ke; Du, Yu; Feng, Chun; Wang, Bi‐Qin; Fang, Dong‐Mei; Chen, Xiao‐Zhen; Ni, Hai‐Liang; Xiang, Shi‐Kai
Abstract: An amide‐directed bay‐region two‐step annulative π‐extension reaction of biphenyls and terphenyls with diaryliodonium salts has been developed. A variety of polycyclic aromatic hydrocarbons can be synthesized efficiently according to this approach, such as triphenylene, dibenzo[ fg, op ]tetracene, and tribenzo[ fg, ij, rst ]pentaphene derivatives. Abstract :